Prevalence of the zoonotic diseases cysticercosis and trichinellosis among pigs in rural Cambodia : a cross-sectional study investigating prevalence and risk factors - Söderberg, Rebecca (SLU/Dept. of Clinical Sciences (until 231231), 2020)
Cysticercosis and trichinellosis are two parasitic zoonoses that are prevalent among pigs in Southeast Asia. The two diseases can cause serious illnesses in humans and human cysticercosis is a leading cause of death from food-borne diseases globally. In Cambodia, the majority of pigs are raised extensively in family backyards in households with between one and four pigs. Pork is the most importance source of meat in this region and is also an important source of income for the farmers. These factors could increase the risk for cysticercosis and trichinellosis in humans in Cambodia, but information regarding the prevalence in rural small-scale pig production is still very limited. This study was conducted in four provinces in north-eastern Cambodia (Kampong Thom, Preah Vihear, Ratanakiri and Stung Treng). The objective was to determine the seroprevalence of porcine cysticercosis and trichinellosis in rural Cambodia, and to identify possible risk factors for both diseases. In total 139 households participated, and 242 blood samples were collected. Only households with less than 10 pigs above three months old were included in the study. For each pig, sex, age and breed were noted. For each household one person was interviewed about food and hygiene habits, management of the pigs, disease knowledge and practice of treatment with antiparasitic medicines. The serum samples were analysed with ELISA for presence of antigens for cysticercosis or antibodies towards trichinellosis. Univariable statistical analyses were used to identify associations between potential risk factors and positivity for cysticercosis and trichinellosis. Positivity among the pigs was 11.2% (95% CI 7.5-15.8) for cysticercosis and 2.5% (95% CI 0.9-5.4) for trichinellosis. Cysticercosis was more common in the province Preah Vihear (p<0.001) than in the other provinces. Management systems for the pigs and access to human faeces were two risk factors significantly associated with porcine cysticercosis (p<0.001). Trichinellosis was more common in the province Ratanakiri (p=0.001). Feeding food waste to the pigs was identified as a risk factor for porcine trichinellosis (p=0.048). Treatment with antiparasitic medicine was identified as a protective factor for trichinellosis (p=0.005). Furthermore, the respondents that had heard of cysticercosis were more commonly men (p=0.002), and were also consuming undercooked pork meat to a greater extent (p=0.004). Province and gender were also significantly (p<0.001) associated with consumption of undercooked pork. Although the present study is relatively small,several risk factors could be identified for porcine cysticercosis and trichinellosis. The results from this study can be used to guide future interventions and studies to improve both porcine but also human health in these provinces. It would however be interesting with further research on the situation in the other regions in Cambodia.